The Employment of Motivation Strategies by ESL Teachers in Language Teaching in the Philippines - GUADAÑA, ROMA MARIAN (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: This paper aims to identify the motivation strategies employed by high school English Language teachers in conducting their lessons in English language teaching. It also aims to examine the relationship between the motivation strategies employed by English Language Teachers and the parts of the lesson in which the strategies are used. Approach/Methodology/Design: Descriptive Correlational Design was employed in this study. Purposive sampling was utilized in the study which comprised of eight English teachers of Pag-asa National High School, Philippines. Mean (X) and Pearson-r were used for the interpretation of data. Findings: The results of the study showed that out of forty eight listed motivation strategies only eighteen motivational strategies are performed by the English teachers. Also, motivation strategies directed to promoting learners’ confidence are mostly utilized by the teachers and the different parts of the lesson are associated with the motivational strategies. The study is limited only to identifying the motivational strategies used by the teachers and how these motivational strategies are related to teaching English in Pag-asa National High School. Practical Implications: This study may aid the teachers in understanding whether they employ enough motivational strategies in their classes. Originality/value: The results of this study may be used as a basis in conducting Learning Action Cell (LAC) Sessions among English teachers in terms of managing English classes and using of motivation strategies.